Student Financial Well-being: Personal Factors and Financial Behavior as Antecedents of Financial Well-being - Margasari, Naning; Andhini, Mega Murti; Musaroh, Musaroh; Bandara, R. A. Seetha (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2024)
AbstractThe information age has the potential for a negative impact on materialism and a positive impact on ways of managing student finances. This can affect the financial well-being of students. This study aims to determine the antecedents of financial well-being in college students in terms of personal and behavioral characteristics. Personal characteristics and behavior are in terms of materialism, financial behavior, and financial self-efficacy variables. These variables are measured through a questionnaire instrument developed from previous research. The results of this study found that materialism and financial behavior had a negative and significant effect on financial well-being, but financial self-efficacy was not proven to have a significant effect on financial well-being. The results of this study provide practical implications in improving student financial well-being, such as through financial literacy to control student materialism and financial behavior. Keywords:Materialism, Financial Behavior, Financial Self-Efficacy, Financial Well-Being.